Analisis Bauran Pemasaran (Marketing Mix) 4P pada Usaha Tahu Ibu Tri Wulandari di Desa Raman Fajar, Lampung Timur - Melani Sintawati; Robi Santoso; Denny Kurniawan (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the implementation of the 4P marketing mix strategy and identify obstacles faced by Ibu Tri Wulandari's home-based tofu enterprise in Raman Fajar Village, East Lampung. Using a descriptive qualitative approach, data were gathered through observation, in-depth interviews, and documentation. The Miles and Huberman interactive model was applied for data analysis, while source and method triangulation ensured validity. Results indicate that all marketing mix elements operate effectively. The product demonstrates superior taste, safety, and hygiene. Competitive pricing at IDR 500 per piece, combined with direct and indirect distribution channels, proves successful. Promotion strategies encompass WhatsApp, Facebook, word-of-mouth, and packaging media. However, operational constraints persist, particularly limited promotional reach that restricts market expansion beyond the local area.